Nuel Belnap on Indeterminism and Free Action. - Müller, Thomas. (Outstanding Contributions to Logic Series, 2014)
Featuring critical assessments of Belnap's work, and a paper by the celebrated philosopher himself on case-intensional first order logic, this selection of original research on a much-debated topic charts his impact on the discussion and builds on his ideas.